Activities of Professor of Riga Polytechnicum / Riga Polytechnic Institute Heinrich Malcher (1848– 1927) and His Contribution to Latvia - Šellers, Daniels; Zigmunde, Alīda; Medveckis, Arturs (History of Engineering Sciences and Institutions of Higher Education, 2024)
In the first decades of its existence, many foreigners worked at Riga Polytechnicum (RP), including one of the most internationally recognized lecturers and scientists, geodesist and hydrotechnician Heinrich Malcher (1848–1927), who continued to work at RP even after the reorganization of the university into Riga Polytechnic Institute (RPI; 1896). For 20 years, the Professor was the Head of the Department of Engineering (1882–1902) of RP / RPI. In addition to his teaching work, H. Malcher designed the water pipeline for Jelgava (1881), led the creation of the first triangulation network of the city of Riga, dealt with the city’s sewage disposal issues, and was an active member of the Riga Technical Society. He spent his twilight years in the Czech Republic, in the village of Kujavy, where he created the first water distribution system and worked as a construction consultant and inspector.